Cross-Protection in Hamsters Immunized with Group A Arbovirus Vaccines - Cole, Francis E. (1971)
Cross-protection between Venezuelan, Eastern, and Western equine encephalomyelitis (VEE, EEE, WEE) viruses was studied in the hamster by using challenge responses and neutralizing antibody titers as indexes of protection. Formalin-inactivated vaccines induced only homologous protection regardless of the sequence of vaccination or the combination of vaccines employed. Use of attenuated VEE vaccine, singly, produced absolute homologous protection as well as 37 and 59% protection against WEE and EEE challenges, respectively. Neither deleterious nor enhancing interaction occurred when attenuated VEE and inactivated WEE and EEE vaccines were employed in various sequences of immunization and all possible combinations. The most rapid and simple immunization scheme eliciting excellent homologous protection consisted of a single dose of combined attenuated VEE and inactivated WEE and EEE vaccines. Studies with attenuated strains of VEE, EEE, and WEE viruses showed that all elicited excellent homologous protection when administered singly. However, use of these live strains in many combinations and sequences resulted in a significant (P < 0.05 to <0.001) decrease in the protective efficacy of the WEE or EEE strains. These results are discussed in relation to serum neutralization test data obtained on sera drawn pre- and postchallenge.